PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU KECELAKAAN LALU LINTAS YANG MENGAKIBATKAN ORANG LAIN MENINGGAL DUNIA BERDASARKAN PUTUSAN NOMOR 73/PID.SUD/2025/PN SBY - Laksono, Dedi Dwi; Subekti, Subekti; Handayati, Nur; Prawesthi, Wahyu (Gapenas Publisher, 2025)
A traffic accident is an unintentional accident on the road involving vehicles with or without other road users, resulting in human casualties and/or property damage. Human casualties include vehicle drivers, vehicle passengers, and/or other road users. Traffic accidents are classified into three categories: minor traffic accidents that only result in damage to vehicles/property, moderate traffic accidents that result in minor injuries and damage to vehicles/property, and finally, serious traffic accidents that result in fatalities or serious injuries. The main issue is: What is the criminal liability of the perpetrator of a traffic accident that causes the death of another person based on Case No. 73/Pid. Sus/2025/PN Sby and what are the judges' considerations in their decision on traffic accidents that result in the death of others based on Case Number 73/Pid.Sus/2025/PN Sby?. The approach used in this study is a normative juridical approach. The normative juridical approach uses legislation, examining all laws and regulations related to the legal issues being addressed. The conceptual approach departs from the views and doctrines that have developed in legal science. Research Results As a result of the defendant's negligence, the victim, Iqbaldi Radhiyallah, died. Therefore, in case number 73/Pid.Sus/2025/PN Sby, the criminal offence of driving a motor vehicle whose negligence caused a traffic accident resulting in the death of another person, the judge convicted the defendant under Article 310 paragraph (4) of Law Number 22 of 2009 concerning Road Traffic and Transportation and sentenced the defendant SI to 2 (two) years and 2 (two) months imprisonment and a fine of Rp. 6,000,000 (six million rupiah).